The Implementation of Spice Route History Material in History Learning in Class XI of SMA Negeri 17 Samarinda - Cahyadewi, Nadya; Marfuah, Siti (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
This study aims to analyze the implementation of the spice route history material in history learning for Grade XI students at SMA Negeri 17 Samarinda. The method used is descriptive qualitative with data collection through direct observation, interviews with teachers and students, and supporting documentation. The findings indicate that the spice route material is not taught as a standalone topic but is combined with discussions on Colonialism and Indonesian National Resistance. As a result, the significance of spices as a world heritage with substantial influence on the economic, cultural, and religious dynamics of the Indonesian archipelago is not adequately addressed in classroom instruction. Consequently, students' understanding of the historical value of the spice route remains limited. Several challenges were identified in implementing this material, including a lack of adequate learning facilities such as relevant media and teaching aids, insufficient time allocation due to a dense curriculum, and limited learning resources-particularly textbooks that comprehensively cover the spice route topic. These issues hinder the effectiveness of the learning process and reduce the quality of material delivery.